Implementasi Metode Pembelajaran Aktif Index Card Match dalam Peningkatan Prestasi Belajar Bahasa Arab Siswa Kelas IV SD Maitreechit Wittayathan School Thailand - Wahyuni Ahmad, Diva Sri; Rudi Setiawan, Hasrian (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims for two main purposes: firstly, to assess the average learning achievement of fourth-grade students at SD Maitreechit Wittayathan School before implementing the Index Card Match method, and secondly, to evaluate the changes in the average learning achievement after the implementation of the Index Card Match method. The research method employed is a classroom action research conducted in two cycles. The research findings indicate that the implementation of the Index Card Match Learning Method can enhance the Arabic language learning achievement of students. In Cycle I, the average student activity reached 54.99%, which then increased to 73.93% in Cycle II, showing an improvement of 18.94%. Additionally, the average student learning outcomes in Cycle I were 61.78%, increasing to 67.5% in Cycle II, with an improvement of 5.72%. Despite the improvement, the percentage of students achieving a score ≥75 still falls short of the desired target of 85%. Based on the research results, 12 students have achieved or exceeded the Minimum Mastery Criteria (KKM), while 2 students have not yet reached mastery. Therefore, further efforts are needed to increase the percentage of students achieving scores above KKM to meet the desired indicators.